Arbitration and Regulation: An Analysis of the Application of Arbitration in the Telecommunications Sector - Santiago, Rafael da Silva (Law, State and Telecommunications Review, 2014)
Purpose ”“ The paper analyzes the possibility of the use of arbitration in disputes that take place in telecommunications sector, proposing alternatives to the regulatory actions of the National Telecommunications Agency ”“ ANATEL. Methodology/approach/design ”“ Considering its qualitative character, the paper aims to describe and interpret the use of arbitration in telecommunications. The approach refers to a documentary research, based on a content analysis, proposing to increase the use of alternative dispute resolution in regulatory policy. Findings ”“ Arbitration can be used in conflicts between agents of telecommunications or in conflicts between one of them and ANATEL. In the second case, only if the agency is performing activities that have clear patrimonial impact, which is inherent to their practice. Practical implications ”“ The paper formulates theoretical tools to base the practice of arbitration in telecommunications sector and provides an illustrative list of activities from ANATEL that can be submitted to arbitration. It also gives suggestions for future arbitrations. Originality/value ”“ The paper provides theoretical basis for the implementation of new ways for dispute resolution in the context of regulation.